Preparation of nutritious drink from date palm kernel(DPK) - Mirghani, Mohamed Elwathig Saeed; Jaswir, Irwandi; Mustapha, Nurul Hanan (IIUM Press, 2011)
This study was carried out to search the potenlial of using dale palm kernel (DPK) as value-added components 10 be included in food products. Date pits (kernels) were used in food industry tu produce edible nutritious DPK drink. After tlte DPK powder was eonfinned to be free from any toxin. the DPK powder was analyzed for the nutritional compounds which resulted in protein 0.9809 mg/g. glucose 0.7351 giL and fructose 0.6 giL Anal~is of the mineral clements in the ash gave the following average values: Cu. 0.9127 mgfg: Ca. 1.0351 mgig; Fe. 0.9108 mg/g: Mil. 0.4285 mgt!!; Mg, 4.99 mgtg and K. 6.74 mgtg. Oil content ....as 8%. The c,~rcrimcnt was continued with the preparation of the DPK drink and the nutrilional values of DPK drink were analyzed in which the differences in the measurement were not very significant. Factorial design was used for the optimization Wilh 3 independent variables which were the volume of ....ater and the amount of sucrose and citric acid. The ma:>limum overall acceptability through the sensory ",aluation was achieved for the OPK drink formulation of 150 ml ....ater. 300 g sucrose and 4 g citric acid with the dilution of 1'3. Analysis of Ihe result was cvaluated by using Ocsign-Expcrt (DX6) software by statisticaltouls.